#### 83hurstguy

##### Member

- Joined
- Sep 18, 2005

- Messages
- 566

True or False

1 = sqrt(1) = sqrt(-1*-1) = sqrt(-1)*sqrt(-1) = j * j = -1

(sqrt is square root, representing a radical... j can also be referred to as i)

- Thread starter 83hurstguy
- Start date

By registering with us, you'll be able to discuss, share and private message with other members of our community.

SignUp Now!You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Joined
- Sep 18, 2005

- Messages
- 566

True or False

1 = sqrt(1) = sqrt(-1*-1) = sqrt(-1)*sqrt(-1) = j * j = -1

(sqrt is square root, representing a radical... j can also be referred to as i)

- Joined
- May 25, 2001

- Messages
- 9,021

And there is no such thing as sqrt -1 unless there's some kind of quantum physics type situation where it could exist.

- Joined
- Sep 18, 2005

- Messages
- 566

sqrt(-1) = j... sqrt(-4) = 2j

j*j = -1, j*j*j = -j , j^4 = 1, j^5 = j once again and the cycle repeats... they actually teach this in high school freshman year algebra these days.

is it a trick question? most likely... its apparently true, but nobody knows either way.

- Joined
- May 25, 2001

- Messages
- 9,021

83hurstguy said:...they actually teach this in high school freshman year algebra these days.

Why?

...its apparently true, but nobody knows either way.

If you can get the teacher's explanation for it being true, please post it. It still seems to me that the equation is saying that all those things are equal and all those things include 1 and -1. So, unless you live in Bizzaro world, it can't be true.

- Joined
- Nov 5, 2004

- Messages
- 120

I think the problem is sqrt(-1*-1)=sqrt(-1)*sqrt(-1)

In the left side, the -1 in multiplied before the root is taken, so it's really just the sqrt of 1.

In the right side, the root is taken before the negative in cancled out.

BTW, I think that "i" or sqrt(-1) is a non-real number. An irrational number is a non-repeating, non-terminating decimal.

But what do I know? I failed calc twice and had to join the military. Thanks for giving us something to thing about.

- Joined
- Sep 18, 2005

- Messages
- 566

anyways... sqrt(-1 * -1) should equal sqrt(-1)*sqrt(-1)...

works with other numbers: sqrt(9*4) = sqrt(9)*sqrt(4) (both equal 6).

I agree with ya though, don't see how its possible; square roots are designed to work with positive numbers, it just goes to show there is a glitch in a theory somewhere, lol.

- Joined
- May 25, 2001

- Messages
- 20,930

You can't take things in parenthesis and then move them outside without consulting your lawyer and Stephen Hawking.

Now go roll a j or buy an old TI calculator and test it out.

- Joined
- Nov 5, 2004

- Messages
- 120

works with other numbers: sqrt(9*4) = sqrt(9)*sqrt(4) (both equal 6)."

that's a good point, but the issue is with the signs not the number.

Consider this:

i=sqrt(-1)

sqrt(-9*-4)= sqrt(36)= +/-6 (can be eaither positive or negative)

sqrt(-9)*sqrt(-4)=i sqrt(9) * i sqrt(4)= i^2* +/-3*+/-2= -1*+/-3*+/-2

From here it could go four ways. (+3 & +2)(+3 & -2)(-3 & +2)(-3 & -2)

-1*3*2=-6

-1*3*-2=6

-1*-3*2=6

-1*-3*-2=-6

so +/-6 is the answer. Kinda shot my self in the foot here

hum... going back to the original question. I still think it's wrong because 1 does not equal -1. The trick is that both one and negative one are possible solutions for the sqrt(-1*-1).

Let us know what the teacher says.

- Joined
- Jun 13, 2002

- Messages
- 2,936

- Joined
- Nov 5, 2004

- Messages
- 120

Remember that 1*1=1 and also -1*-1=1

So I could say that "1=sqrt(1)=-1" and looking at only one side (ignoring eaither the 1 or -1) at a time the equation seems true. I think the correct way to express this is sqrt(1)=+/-1.

- Joined
- Nov 5, 2004

- Messages
- 120

9

2K

25

4K

- Members online
- 30

- Guests online
- 342

- Total visitors
- 372

Totals may include hidden visitors.